Mediation Role of Work Life Balance on The Effect of Perceived Organization Support on Lecturer Job Satisfaction at Private University in Jakarta during Covid-19 Pandemic - Nurul Huda; Dian Kemala Putri; Djamalludin Ancok (Asian Social Work Journal, 2023)
The changes occurred during Covid-19 pandemic forced lecturers to be able to do their jobs well and to create a creative and innovative learning atmosphere. In order to make them continuing their duties properly during Covid-19 pandemic, they have to be able to feel job satisfaction. This study aims to examine the effect of perceived organizational support on job satisfaction in lecturers during Covid-19 pandemic through work life balance. The respondent consisted of 184 respondents with the criteria being lecturers who teach at private university in Jakarta and at least have a Master Degree. Data analysis used SPSS version 23 and SmartPLS version 3.2.9. The results of this study state that work life balance mediates the effect of perceived organization support on job satisfaction with a coefficient value of 0.055 and a t-statistic value of 3.136 > 1.96 with a p-value of 0.002 (ρ<0.05) and significant. This proves that work life balance plays role as a variable that mediates between perceptions of organizational support and job satisfaction in private university lecturers during Covid-19. These results have implications that need to develop a policy to create a good work life balance for lecturers by minimizing the role conflicts that occur and further improve support for lecturers so expectations of job for lectures are created.